Analisis Industri Farmasi Indonesia Dalam Menghadapi Pemberlakuan Masyarakat Ekonomi ASEAN (AEC) Tahun 2015 - , Ganggas Cahyono ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Pharmaceutical Industry in Indonesia is one of few industries that always growth with average more than 10% annually with domestic market orientation. The pharmaceutical industry growth in Indonesia is supported by population growth, longer life of population, and increasing in spending for health per capita in years. This research purpose is to analyze the structure, performance, and cluster of pharmaceutical industry in Indonesia. Pharmaceutical industry structure is analyzed by concentration ratio from output of pharmaceutical industry in Indonesia. Pharmaceutical industry performance is analyzed by analyzing productivity, efficiency, contribution of pharmaceutical industry output with total output of manufacturing industries in Indonesia, export of pharmaceutical industry with total export of manufacturing industries in Indonesia, and total export with total output of pharmaceutical industry. Cluster of pharmaceutical industry is analyzed by analyzing output, added value, labors, and total pharmaceutical companies which operate in islands, provinces, regions/cities, and extended industrial areas. Some recommendations are also given at end part of this research for government and pharmaceutical business people to enhance the competitiveness and maintain the sustainability growth of Indonesia pharmaceutical industry toward ASEAN Economic Community (AEC) implementation in 2015.